Nowa polityka spójności Unii Europejskiej szansą dla wzrostu gospodarczego i wzrostu zatrudnienia w jej regionach - Klamut, Mirosława (The New Cohesion Politics of the European Union as a Chance for Economic Growth and Increase of Employment, 2007)
The goal of this elaboration is to indicate significance of the cohesion politics of the European Union in the strengthening of its integration process. The author analyzes circumstances for the cohesion politics after the year 1987, i.e. since the European Union decided to speed up the process of entering the Economic and Unitary Union. Particular attention is also put to analyze the conditions for realization of the cohesion politics in the next period for the years 2007-2013. Then, the Union will, after expanding with significantly less developed countries, challenge its cohesion politics when all member countries will be obliged to adjust their macroeconomic politics to the criteria of convergence. The new adjustments will be needed for effective realization of the cohesion politics both in budgeting (substantial increase) and in the process of programming of the development in the Union. The adjustments should increase competitiveness of the regional economies, but first of all, they should speed up structural changes needed for modernization of the European economy and for creating new and highly effective jobs.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 11-26